Effect of picung (Pangium edule) plant extracts as a botanical pesticide on mortality of coffee berry borer (Hypothenemus hampei) - soekadar wiryadiputra (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Coffee pests known as coffe berry borer (CBB, Hypothenemus hampei) were main pests which decreasing the productivity of Indonesian coffee. One of pests controlling was done by insecticides. Generally, plant uses for insecticide show high security level, because the breaking molecule was easy as not dangerous compound. Pangium edule contains of flavanoide, cyanide acid and saponin had potential as an botanical insecticide. The purpose of this research was to prove the potential extract of seed and leaves of picung (Pangium edule) as an botanical insecticide for CBB. This research used a complete random design. There were 8 treatments with the concentration of the extract from leaves and seed of picung, one positive control treatment (Carbaril 0,02% formulation) and one negative control treatment (aquades). The treatment was repeated four times and carried out observation on every day until six days. The concentrations leaf and seed extracts were 1.0%, 2.5% and 5.0%. The result of the research show that between concentration applied the were no significant different and at observation six days after application the mortality of CBB only around 35 -40% on both extracts (ewater and methanol). The result of the research also show that there were no real differentiation between leaves and seed of picung. LT-50 values were 1.25% and 0.96%, for leaves and seed extract in water for six day observation. From this observation could be concluded that picung tree (Pangium edule) is not effective in the controlling CBB in the interval concentration applied and extraction method used. Key words: Botanical pesticide, picung tree, Pangium edule, mortality, Hypothenemus hampei, water extraction, methanol extraction.